Incidence of post-operative urinary retention in patients undergoing lower limb surgeries under spinal anesthesia: A prospective study - Rohey Jan; Salma Mariyam; Malik Nasir; Anjum Rashid; Aprajita; Mohsin Fayaz; Mehak Khan (Asian Journal of Medical Sciences, 2025)
Background: Postoperative urinary retention (POUR) is a troublesome postoperative complication in which after surgery, a patient cannot urinate even when the bladder is completely filled. Sometimes, POUR is not appropriately recognized and causes considerable distress in patients and susceptibility to urinary tract infection and subsequent increased risk of deep joint sepsis in orthopedic surgeries. Aims and Objectives: To determine the incidence and risk factors of POUR in lower limb surgeries under spinal anesthesia, focusing on surgical type, patient demographics, and perioperative factors. In addition, to analyze POUR’s association with joint replacement and trauma-related surgeries and its impact on bladder function and catheterization needs. Materials and Methods: A prospective, single-center, observational study was conducted at a tertiary care referral center in North India, i.e. January–September 2022–March 2023 after approval from an institutional ethical committee. The study group enrolled 168 patients undergoing various lower limb surgeries under spinal Anesthesia. Results: In the present study, out of 168 patients, there was a male preponderance (96 patients were male and 72 were female). Most of the patients were in the 35–60 years age group (78) followed by 72 patients were in the >61-year age group. 21 patients (11.29%) suffered from POUR in whom catheterization was required. The incidence of POUR was higher in joint replacement surgeries 20.96% (13/62). In the present study, incidence of POUR was more in males (23 patients) as compared to females (12 patients) and more common in the elderly age group. Conclusion: The incidence of POUR is higher in males, elderly patients, and individuals undergoing joint replacement surgery.